PENGARUH EKSPRESI RESEPTOR INSULIN PANKREAS TERHADAP EKSPRESI GLUT4 NEURON HIPOKAMPUS PADA TIKUS MODEL DIABETES - Sahly, Aliza Raudatin; Hunaifi, Ilsa; Lestari, Rizka Vidya; Wardani, Indah Sapta; Padauleng, Novrita; Nurhidayati; Harahap, Herpan Syafii (Faculty of Medicine Universitas Mataram, 2020)
Background: Diabetes Melitus (DM) is a degenerative diseases characterized by hyperglycemia condition. Basic Health Research data for 2018, shows an increase in prevalence of DM in Indonesia over last 5 years with 6,9% in 2013 to 8,5% in 2018. Pancreatic insulin receptor expression can be a marker for assessing presence of ? cells, production and secretion of insulin. Insulin could cause GLUT4 to be translocated to cell membrane of hippocampal neurons. In DM conditions, there may be changes in expression of pancreatic insulin receptors accompanied by changes in expression of GLUT4 hippocampal neurons. Methods: This experimental research used 16 white rats (Rattus Novergicus) which divided randomly into 4 groups, namely 2 control grups (A0 and A1) and 2 treatment groups (B0 and B1). Treatment group were induced by diabetes with a single dose of nicotinamide 110 mg/kgBB and streptozotocin 70 mg/kgBB intraperitoneally. The research data were obtained from immunohistochemical analysis of pancreatic and hippocampal tissue. Result: The mean expression of pancreatic insulin receptor in diabetic rat group was higher but not significant on the 14th day observation compared to the 0th day (p>0,05), while the mean GLUT4 expression of hippocampal neurons was significantly higher on 14th day of observation compared to the 0th day (p<0,05). The result of correlation test did not show a significant results in each group both at the 0th and 14th day observation (p>0,05). Conclusion: There was no significant effect of pancreatic insulin receptor expression on hippocampal neuron GLUT4 expression in diabetic model rats.